Photoluminescence behavior on Sr2+ modified CaCu3Ti4O12 based ceramics - Orrego, S. [UNESP] (2018)
Sr2+ modified CaSrxCu3-xTi4O12 ceramic powders with x = ranging from 0.00 to 3.00 were prepared by solid-state reaction. The effects of Sr2+ CCTO powders were evaluated by X-ray diffraction (XRD) with Rietveld refinement revealing a mixture of multiple phases. The Raman spectroscopy analysis pointed out that Sr2+ addition produces an emission in the blue region, associated to TiO6 clusters. Optical properties by means of PL analysis showed emission near to blue region for the samples with x = 0.00, x = 0.15, x = 0.30, corresponding to oxygen vacancies. The emission in the violet region is associated to deep defects while emission in the other samples is linked to shallow defects typical of disordered crystalline structures. Less prominent emission in the green region with the increase of Sr2+ corresponds to less self-trapped charges, less interaction between electron and hole, and donor–acceptor recombination.